2013
DOI: 10.1002/hep.26654
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles encapsulating hepatitis B virus cytosine-phosphate-guanosine induce therapeutic immunity against HBV infection

Abstract: Infection with hepatitis B virus (HBV) is the most common cause of liver disease worldwide. However, because the current interferon (IFN)-based treatments have toxic side effects and marginal efficacy, improved antivirals are essential. Here we report that unmethylated cytosine-phosphate-guanosine oligodeoxynucleotides (CpG ODNs) from the HBV genome (HBV-CpG) induced robust expression of IFN-a by plasmacytoid dendritic cells (pDCs) in a Toll-like receptor 9 (TLR9)-dependent manner. We also identified inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 32 publications
(68 reference statements)
0
24
0
Order By: Relevance
“…In addition, the number of pDCs has been previously reported to be reduced in vivo during several systemic viral infections including HBV [37]. In one of the most recent reports, Lv et al [38], showed that HBV-derived CpG induces potent IFN-α production by human pDCs, which may partially explain how pDCs interact with HBV in infection. However, the cause of weak participation in the early response of IFN induction in Myd88 -/- mice remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the number of pDCs has been previously reported to be reduced in vivo during several systemic viral infections including HBV [37]. In one of the most recent reports, Lv et al [38], showed that HBV-derived CpG induces potent IFN-α production by human pDCs, which may partially explain how pDCs interact with HBV in infection. However, the cause of weak participation in the early response of IFN induction in Myd88 -/- mice remains to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…In one study, endogenous HBV-CpG oligodeoxynucleotides from the HBV genome stimulated IFN-a production by pDCs in a TLR-9-dependent manner, thus resulting in the clearance of HBV in HBV carrier mice [50]. The importance of TLR9 signaling has also been reported in other mice models where it induced the intrahepatic aggregates of myeloid cells and efficiently supported local proliferation of effector CD8 ?…”
Section: Immunological Intervention Against Hbv Infectionmentioning
confidence: 88%
“…Combined with rHBsAg immunization, administration of nanoparticles containing HBV-CpG led to the clearance of HBV and induced an anti-HBsAg response in HBV carrier mice. 64 Along the same lines, Wu et al demonstrated that intrahepatic administration of TLR3 ligand poly(I:C) could recruit CD8 1 T cells into the liver and clear HBV in an IFN-and CXCR3-dependent manner. 65 These studies indicate that TLR agonists may be used as immunomodulatory agents for the treatment of chronic HBV infection by augmenting the HBV-specific T-or B-cell responses.…”
Section: Activation Of Tlr-mediated Signaling Pathways Modulates Hbv-mentioning
confidence: 96%